2017
DOI: 10.1002/2016ja023306
|View full text |Cite
|
Sign up to set email alerts
|

Io plasma torus ion composition: Voyager, Galileo, and Cassini

Abstract: The Io torus produces ultraviolet emissions diagnostic of plasma conditions. We revisit data sets obtained by the Voyager 1, Galileo, and Cassini missions at Jupiter. With the latest version (8.0) of the CHIANTI atomic database we analyze UV spectra to determine ion composition. We compare ion composition obtained from observations from these three missions with a theoretical model of the physical chemistry of the torus by Delamere et al. (2005). We find ion abundances from the Voyager data similar to the Cass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 81 publications
(199 reference statements)
4
46
1
Order By: Relevance
“…Meanwhile, the relative composition of sulfur ion charge states observed by Cassini ( Figure 4C) has an enhanced relative abundance of S 3+ than at Juno (33% versus 9% of sulfur ions), while S + and S 2+ decreased in relative flux abundance for sulfur ions at Cassini compared to at Juno (25% versus 29% for S + and 42% versus 62% for S 2+ ). shown Bodisch et al, 2017;Nerney et al, 2017), along with a forward model of Juno JADE-I observations (Kim et al, 2019). While each of these studies makes its own assumptions (e.g., assuming the density of O 2+ is 10% that of O + in Yoshioka et al, 2017) and has its own uncertainties, caveats, spatial coverages, and energy ranges, the results are seen to qualitatively agree in regard to the relative order of abundance of the species.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Meanwhile, the relative composition of sulfur ion charge states observed by Cassini ( Figure 4C) has an enhanced relative abundance of S 3+ than at Juno (33% versus 9% of sulfur ions), while S + and S 2+ decreased in relative flux abundance for sulfur ions at Cassini compared to at Juno (25% versus 29% for S + and 42% versus 62% for S 2+ ). shown Bodisch et al, 2017;Nerney et al, 2017), along with a forward model of Juno JADE-I observations (Kim et al, 2019). While each of these studies makes its own assumptions (e.g., assuming the density of O 2+ is 10% that of O + in Yoshioka et al, 2017) and has its own uncertainties, caveats, spatial coverages, and energy ranges, the results are seen to qualitatively agree in regard to the relative order of abundance of the species.…”
Section: Resultsmentioning
confidence: 90%
“…Meanwhile, both Yoshioka et al () and Steffl et al (2004b) used remote sensing (Hisaki EUV and Cassini UVIS, respectively). Lastly, three studies of reanalysis from forward modeling of Voyager PLS observations are shown (Bagenal et al, 2017; Bodisch et al, ; Nerney et al, ), along with a forward model of Juno JADE‐I observations (Kim et al, ). While each of these studies makes its own assumptions (e.g., assuming the density of O 2+ is 10% that of O + in Yoshioka et al, ) and has its own uncertainties, caveats, spatial coverages, and energy ranges, the results are seen to qualitatively agree in regard to the relative order of abundance of the species.…”
Section: Resultsmentioning
confidence: 99%
“…At the center of the torus, we estimate the timescale for energy loss from a 100 eV beam would be approximately 250 h (Huba, 2009;Nerney et al, 2017). At the center of the torus, we estimate the timescale for energy loss from a 100 eV beam would be approximately 250 h (Huba, 2009;Nerney et al, 2017).…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 97%
“…We modify Model A to account for a recent reanalysis of the Voyager data by Bagenal, Dougherty, et al (). Model‐scale heights are updated due to composition and temperature changes found by Bagenal, Dougherty, et al () and Nerney et al (). Model densities are updated due to reanalysis of Voyager data by Bagenal, Dougherty, et al ().…”
Section: Perijove 1 Comparison To Voyager Modelsmentioning
confidence: 99%